EVALUASI IMPLEMENTA SI SISTEM ELECTRONIC HEALTH RECORD (EHR) DI RUMAH SAKIT AKADEMIK UNIVERSITA S GADJAH MADA BERDASARKAN METODE ANALISIS PIECES - Erna Adita Kusumawati; Sri Sugiarsi (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2015)
The purpose of this study was to evaluate an Electronic Health Record (EHR) at the Academic Hospital ofthe University of Gadjah Mada reviewed based on the PIECES method analysis to determine the aspectsof performance, information / data, economic, control, efficiency, and service. This study used descriptiveresearch with quantitative approach and cross-sectional study design. The result of the research showed Aspectsperformance (performance), information / data (information / data), efficiency (efficiency), service (leyanan)Academic Hospital EHR system UGM rated as good by users of EHR systems, while aspects of control /security (control / security) considered quite good and economic aspects (economic) Academic Hospital EHRsystem UGM rated poorly by users of EHR systems. While the EHR system in UGM Academic Hospital whenviewed from the characteristics of users with various categories of age, past education, tenure, and work unitshowed different results in every aspect of the study (performance, information / data, economic, control /security, efficiency, service).Keywords: evaluation, implementation, Electronic Health Record, PIECESAbstrakTujuan penelitian ini adalah melakukan evaluasi sistem Electronic Health Record (EHR) di Rumah SakitAkademik Universitas Gadjah Mada ditinjau berdasarkan metode analisis PIECES untuk mengetahui aspekperformance, information/data, economic, control, efficiency, dan service. Penelitian ini menggunakan metodepenelitian deskriptif dengan pendekatan kuantitatif dan rancangan penelitian cross sectional. Hasil penelitianmenunjukkan Aspek performance (kinerja), information/data (informasi/data), efficiency (efisiensi), service(leyanan) sistem EHR di RS Akademik UGM dinilai baik oleh pengguna sistem EHR, sedangkan aspek control/security (kontrol/keamanan) dinilai cukup baik dan aspek economic (ekonomi) sistem EHR di RS AkademikUGM dinilai kurang baik oleh pengguna sistem EHR. Sedangkan sistem EHR di RS Akademik UGM apabiladitinjau dari karakteristik pengguna dengan berbagai kategori usia, pendidikan terakhir, masa kerja, dan unitkerja menunjukkan hasil yang berbeda dalam setiap aspek yang diteliti (performance, information/data,economic, control/security, efficiency, service).Kata kunci: evaluasi, implementasi, Electronic Health Record, PIECES